"Rapprocher les lieux du pouvoir": The Québec Labour Movement and Québec Sovereigntism, 1960-2000 - Güntzel, Ralph P. (Labour / Le Travail, 2000)
The article examines the evolution of Quebec's three major trade union federations–the Federation des travailleurs et travilleuses du Québec, the Centrale des syndicats nationaux, and the Centrale des syndicats du Québec–on the question of Quebec sovereignty since 1960. In the course of the four decades since the emergence of the modem sovereignty movement, the three federations adopted increasingly sympathetic attitudes and eventually became stalwarts of the sovereignty coalition. In the process Quebec labour activists shed their fears about the economic repercussions of sovereignty and espoused the notion of a sovereign nation-state, mainly because they came to see it as a way to implement social-democratic and labour-oriented policies.
Keywords: FEDERATION des travailleurs et travailleuses du Quebec